Production performance, carcass characteristics, intestinal morphometry and serum biochemistry in dual purpose chicken fed diet incorporated withrice distillers grain with soluble - DAS, TAPAN KUMAR; KAR, DEBALINA; ROY, BARUN; DEBNATH, BIKAS CHANDRA; DEBNATH, JOWEL; SARKAR, BIJOY KUMAR; DEBROY, BIPLAB; CHAKRABORTY, DIBYENDU (The Indian Journal of Animal Sciences, 2024)
This study investigated the effects of rice distillers grains with solubles (rDDGS) on growth performance, production efficiency, carcass characteristics, nutrient metabolizability and serum biochemistry of dual purpose chicken (Kuroiler). Four diets were formulated with graded levels of rDDGS (0, 10, 14 and 18%). Each diet was allocated to 5 replicates with 10 birds in each at random. With the exception of 21 days, there was no difference in body weight gain, feed intake, or feed conversion ratio (FCR) among the treatment groups. The dietary levels of rDDGS had no effect on serum biochemical parameters. Dietary level of 14% rDDGS significantly increased dressing yield and thigh and drumstick percentage. The metabolizability of dry matter, crude protein, ether extract, crude fiber, nitrogen free extract and organic matter was similar among the experimental groups. The addition of rDDGS had no negative effects on jejunum histo-morphometry. In the 18% rDDGS fed group, profit per kg live weight was comparatively higher. In conclusion, rDDGS may be added to dual-purpose chicken diets safely up to an 18% inclusion level as a substitute protein source for profitable production.